When a child dies parents' lived experiences of bereavement by sudden loss - Ayaso, Regina D.; Cumla Audrey L.; Ecija Normae C.; Inciso, Jedediah Marianthe A.; Octa, Marinel L. (Regina D. Ayaso, Audrey L. Cumla, Normae C. Ecija, Jedediah Merianthe A. Inciso, Marinel Octa, 2014)
The purpose of the study is to discover and describe the lived experiences of bereaved mothers and fathers who lost a child through a sudden death. The death of a child by sudden loss is deemed as one of the most intense and challenging part of a parent's life. Six participants of this study were identified using purposive sampling. Interviews were conducted to generate data and then analyzed using thematic analysis. The results revealed three major themes namely grief reactions, living with bereavement, and resolution. Moreover, gender differences in terms of grieving and coping has been observed in the study. This led to a conclusion that parents experience different reactions, grieve differently and make meaning in various ways.